Combined effect of salinity and pollution with potassium dichromate on adaptive capacity of diatom benthic microalga Attheya ussurensis in laboratory environment - Nina A. Aizdaicher; Olga B. Gostyukhina (Известия ТИНРО, 2015)
Combined effect of two stress factors (decreasing of salinity and presence of potassium dichromate in the medium) on adaptive capacity of benthic alga Attheya ussurensis is investigated. The salinity decreasing to 20 ‰ combined with 0.01 mg/L of K2Cr2O7 in the medium didn’t cause any change of the cells growth in number, as compared with uncontaminated environment (32 ‰, control), or changes in their morphology. The same salinity decreasing with K2Cr2O7 concentration 0.10 mg/L caused a lowering of the cells growth to 86 % of the control value by the end of experiment that was accompanied by minor morphological abnormalities, as cells elongation in pervalvar axis direction and granulation of chloroplasts. In the second seeding, there was no change of the cells growth again under the low concentration of K2Cr2O7 and their adaptation to the concentration 0.10 mg/L was observed: in the end of experiment the cells number had no significant difference from the control one. The salinity decreasing to 16 ‰ with the toxicant concentration 0.01 mg/L caused a lowering of the cells growth in the 4th day that persisted until the end of experiment and some insignificant changes of their morphology. The same salinity decreasing with the toxicant concentration 0.10 mg/L caused a significant drop of the cells number with strong negative morphological changes; moreover, the alga wasn’t able to adapt to this combined stress after re-seeding.